The bisphosponates: chemical characteristics, skeletal biological effects and extra-skeletal effects - F.P. Cantatore; A. Corrado (Reumatismo, 2011)
Bisphosphonates (BP) are pharmacological compounds whose the most important biological effect is the reduction of bone remodelling, explaining the reason for their use in pathological conditions characterised by an increased bone resorption, such as osteoporosis, Paget’s disease of bone, malign hypercalcemia during myeloma and osteolytic bone metastasis. Nevertheless there are several experimental evidence that BP possess different extra-skeletal biological effects, ranging from analgesic properties, anti-inflammatory and pro-inflammatory effects and the capacity of modifying the biological activity of cells other than osteoblasts and osteoclasts, such as the immune system cells and other cells of mesenchymal origin. Several data report the beneficial effects of BP as anti-inflammatory agents in different inflammatory chronic articular diseases, which make BP suitable drugs for treatment of pathologies other than bone disease